Chronic heart failure is characterized by altered mitochondrial function and structure in circulating leucocytes - Coluccia, Roberta (Oncotarget, 2018)
Oxidative stress is currently viewed as a key factor in the genesis and progression of Heart Failure (HF). The aim of this study was to characterize the mitochondrial changes linked to oxidative stress generation in circulating peripheral blood mononuclear cells isolated from chronic HF patients (HF_PBMCs) in order to highlight the involvement of mitochondrial dysfunction in the pathophysiology of HF. To assess the production of reactive oxygen species (ROS), mitochondrial function and ultrastructure and the mitophagic flux in circulating PBMCs we enrolled 15 patients with HF and a control group of ten healthy subjects. The HF_PBMCs showed a mitochondrial population consisting of damaged and less functional organelles responsible of higher superoxide anion production both at baseline and under in vitro stress conditions, with evidence of cellular apoptosis. Although the mitophagic flux at baseline was enhanced in HF_PBMCs at level similar to those that could be achieved in control PBMCs only under inflammatory stress conditions, the activation of mitophagy was unable to preserve a proper mitochondrial dynamics upon stress stimuli in HF. In summary, circulating HF_PBMCs show structural and functional derangements of mitochondria with overproduction of reactive oxidant species. This mitochondrial failure sustains a leucocyte dysfunctional status in the blood that may contribute to development and persistence of stress conditions within the cardiovascular system in HF.